2012
DOI: 10.1001/archsurg.2012.1649
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Open Operation for Aortoiliac Occlusive Disease After Failed Endovascular Therapy

Abstract: To compare patient outcomes of primary open operation for aortoiliac occlusive disease (AIOD) with those of secondary open operations for failed endovascular therapy (ET) of AIOD. Design: A retrospective cohort study was performed analyzing demographic characteristics, comorbidities, and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
4
11
0
3
Order By: Relevance
“…Nonetheless, we believe that selective ITA territory angiography is advisable in PAD and in the absence of femoral pulse, ITA harvesting should be avoided. In contrast with aortic and renal atherosclerotic involvement, prophylactic lower extremity revascularisations in patients with PAD concomitant with CABG are not justified [42].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, we believe that selective ITA territory angiography is advisable in PAD and in the absence of femoral pulse, ITA harvesting should be avoided. In contrast with aortic and renal atherosclerotic involvement, prophylactic lower extremity revascularisations in patients with PAD concomitant with CABG are not justified [42].…”
Section: Discussionmentioning
confidence: 99%
“…Danczyk et al reported a better survival in patients undergoing redo AbF bypass grafting compared with those undergoing primary operation despite a higher percentage of cardiac risk factors. 24 The reason that a much more invasive operation has better clinical outcomes lies in the fact that redo patients, at that time, were on a better medical regimen; this may underline the importance on outcomes during primary operation, and it could be a coexplanation of the literature and personal results. Last but not least, it confirms that in contrast to infrainguinal distal revascularization, endovascular-first treatment does not preclude an effective open rescue; this is also supported by the findings of Patel et al, who demonstrated that endovascular surgery has not appreciably increased the complexity of open aortic operations performed for AIOD.…”
Section: Discussionmentioning
confidence: 99%
“…Nach erfolgloser Angioplastie sollen die chirurgischen Ergebnisse wesentlich schlechter sein als nach primärer Bypassanlage (256). Dies konnte für aortoilicale (266) und distal-origin Bypasses bei CLI nach erfolgloser femoropoplitealer Angioplastie (429) aber nicht bestätigt werden. Andere Autoren beschreiben für die Erstanlage eines Bypasses signifikant bessere Ergebnisse als für die Bypasschirurgie sowohl nach vorheriger infrainguinaler Angioplastie als auch nach einer vorhergehenden Bypassanlage (430).…”
Section: Gefäßchirurgie Nach Gescheiterter Endovaskulärer Revaskulariunclassified